Apresentação - Dutra e Silva, Sandro; Silva, Iransé Oliveira; Pereira, Natasha Sophie; Ganga-Contreras, Francisco Anibal (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
Apresentação